EFEKTIVITAS PELAKSANAAN PROGRAM DAY CARE SERVICES (PELAYANAN HARIAN LANJUT USIA) OLEH UNIT PELAKSANA TEKNIS (UPT) PELAYANAN SOSIAL LANJUT USIA WILAYAH BINJAI DAN MEDAN - ISNAMULI OKTAVIA B (Welfare StatE, 2012)
Life expectancy Indonesia from year to year continues to increase along with improved quality of life and health care also improved. This affected the increasing number of elderly people in Indonesia, which if not addressed will arise various problems. Among them is the emergence of a variety of demands in order to meet the needs and address the issues related to elderly. Taking into account these problems, the government formulated policies, and service programs for the elderly, one of which is a program of day care services. The program is aimed at seniors who are outside the home, and temporary conducted at noon in the social institutions or outside social institutions in a given time, or the government-run professionally. The research was conducted at the Technical Implementation Unit (UPT) Elderly Social Services Regional Binjai and Medan. This study uses descriptive quantitative approach. To obtain the necessary data, this study used data collection techniques and field studies literature consisting of distributing questionnaires (questionnaire), interview and observation. Keywords: effectiveness, day care services, elderly.